PENGARUH FAKTOR-FAKTOR KUALITAS PELAYANAN TERHADAP KEPUASAN ANGGOTA DI LEMBAGA KEUANGAN MIKRO SYARIAH - Rizal Mahendra Putra; Arif Julanto Sri Nugroho; Anis Marjukah; Titik Purwanti (JURNAL ILMIAH EDUNOMIKA, 2026)
The purpose of this study was to determine the effect of service quality, consisting of factors, on member satisfaction at the Islamic microfinance institution BMT Samara Sukoharjo, both partially and simultaneously, and to determine the most dominant service quality factors. This study used a quantitative descriptive method accompanied by hypothesis testing. The population was all BMT Samara members. The research sample consisted of 80 respondents drawn using a random sampling technique. Data collection used a questionnaire, the results of which were tested for validity and reliability. Data analysis used multiple regression analysis, the F test, the t test, and the coefficient of determination test. The results showed that: There is a significant influence of service quality, consisting of tangibles, reliability, responsiveness, assurance, and empathy, on member satisfaction. This is evident from the results of the regression analysis, which obtained a calculated F value > F table (30.744 > 2.45) at a significance level of 5%. This means that providing direct evidence of service, staff reliability in providing service, staff accuracy in responding to customer complaints, providing service guarantees, and paying attention to customer complaints lead to customer attention and loyalty to the company. The reliability dimension is the dimension that has the most influence on customer satisfaction. This can be seen from the calculated t-value for the reliability dimension (4.004), which is higher than the calculated t-value for the other dimensions: tangibles (3.106), responsiveness (3.779), assurance (2.614), and empathy (3.188). This indicates that reliable service delivery leads to satisfaction among BMT Samara members.  Keywords: service quality, member satisfaction